2009
DOI: 10.1037/a0017398
|View full text |Cite
|
Sign up to set email alerts
|

Generation and perceptual implicit memory: Different generation tasks produce different effects on perceptual priming.

Abstract: The generation manipulation has been critical in delineating differences between implicit and explicit memory. In contrast to past research, the present experiments indicate that generating from a rhyme cue produces as much perceptual priming as does reading. This is demonstrated for 3 visual priming tasks: perceptual identification, word-fragment completion (WFC), and word-stem completion (WSC). This result occurred regardless of the mode of study response (written or spoken) or whether the generation conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 81 publications
(262 reference statements)
2
14
1
Order By: Relevance
“…Consequently, they concluded that most semantic generation tasks produced robust priming on perceptual identifi cation. Regardless of the mode of study response, Mulligan and Dew (2009) also found that semantic priming produced full priming effect on perceptual identifi cation. These results suggest that covert visualization through semantic context is consistent with data-driven proce sses ( Barnhurst et al , 2004 ;Mulligan and Dew, 2009 ).…”
Section: Visual Primingmentioning
confidence: 88%
See 4 more Smart Citations
“…Consequently, they concluded that most semantic generation tasks produced robust priming on perceptual identifi cation. Regardless of the mode of study response, Mulligan and Dew (2009) also found that semantic priming produced full priming effect on perceptual identifi cation. These results suggest that covert visualization through semantic context is consistent with data-driven proce sses ( Barnhurst et al , 2004 ;Mulligan and Dew, 2009 ).…”
Section: Visual Primingmentioning
confidence: 88%
“…Fazio et al (1983) found that individuals exposed to visual cues were found to be primed to retain that information in forming opinions. Given that a visual cue is typically used as a prime, processing the visual feature of the cue may also drive priming on the associated context ( Mulligan and Dew, 2009 ). Such a notion is consistent with the role that shape representation typically plays in perceptual priming ( Biederman and Cooper, 1991 ).…”
Section: Csr Practices and Sctmentioning
confidence: 88%
See 3 more Smart Citations